Refined statistical modeling for chloride permeability and strength of concrete containing metakaolin. (1st July 2016) - Al-alaily, Hossam S.; Hassan, Assem A.A.
Highlights: Optimize chloride permeability and strength was performed in concrete with MK. Total binder content, percentage of metakaolin, and W/B ratio were considered. Statistical models and design charts were developed. The developed models and charts are beneficial for mixture proportions prediction. Abstract: An experimental investigation was conducted to develop design tools using refined statistical analysis to optimize chloride permeability and strength of concrete containing metakaolin (MK). The study adopts the design of experiments (DOEs) to test 53 concrete mixtures based on enhanced response surface method (RSM). Three factors were considered: total binder content (binder), percentage of metakaolin (MK%), and water-to-binder ratio (W/B). The mixtures were examined based on the rapid chloride permeability test (RCPT), chloride diffusion test, compressive strength ( f c ), modulus of elasticity (MOE), splitting tensile strength (STS), flexural strength (FS), and cost of mixture per cubic meter. The developed statistical models and design charts are valid for concrete with W/B ratios ranging from 0.3 to 0.5, MK from 0% to 25%, and total binder content from 350 kg/m 3 to 600 kg/m 3 . The results endorse that the obtained derived models and design charts are useful for understanding the influence of the key factors on concrete mechanical and durability properties. These models and design charts are beneficial for predicting and selecting the optimum mixture proportions for a given application in a simple and accurate way. This paper's recommendations can be of special interest to designers considering the use of concrete containing MK in structural applications.